2020
DOI: 10.1155/2020/8835353
|View full text |Cite
|
Sign up to set email alerts
|

Effects of DMSO on the Pluripotency of Cultured Mouse Embryonic Stem Cells (mESCs)

Abstract: DMSO is a commonly used solvent in biological studies, as it is an amphipathic molecule soluble in both aqueous and organic media. For that reason, it is the vehicle of choice for several water-insoluble substances used in research. At the molecular and cellular level, DMSO is a hydrogen-bound disrupter, an intercellular electrical uncoupler, and a cryoprotectant, among other properties. Importantly, DMSO often has overlooked side effects. In stem cell research, the literature is scarce, but there are reports … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The proteins octamer-binding transcription factors 3 and 4 (Oct-3/4) and NANOG homeobox (NANOG) were evaluated using Western blot. mESCs (cell line E14Tg2a) cultured in 2i medium were used as the positive control [ 62 ]. The protocol was performed as previously described in [ 57 ].…”
Section: Methodsmentioning
confidence: 99%
“…The proteins octamer-binding transcription factors 3 and 4 (Oct-3/4) and NANOG homeobox (NANOG) were evaluated using Western blot. mESCs (cell line E14Tg2a) cultured in 2i medium were used as the positive control [ 62 ]. The protocol was performed as previously described in [ 57 ].…”
Section: Methodsmentioning
confidence: 99%
“…Dimethyl sulfoxide (DMSO) is a frequently employed solvent due to its capacity to dissolve a diverse array of compounds. Nevertheless, it is essential to take into account the potential toxicity of DMSO itself, especially at higher concentrations [30]. In the case of 10% DMSO, it is generally considered a relatively high concentration for use in the brine shrimp lethality assay.…”
Section: Assessment Of Biocompatibility and Toxicitymentioning
confidence: 99%
“…Although there are various advantages and many biocompatibility experiments have been performed, only a few clinical trials have been reported in the literature, and regulatory agencies such as the FDA and EMA have not approved any devices [ 227 ]. The reason may be that the toxic solvents used in the electrospinning process probably have a small number of residues and release together with the drugs.…”
Section: Application Fieldsmentioning
confidence: 99%